Effects of Milling Methods and Cultivars on Physicochemical Properties of Whole-Wheat Flour - Min Jeong Kang; Mi Jeong Kim; Han Sub Kwak; Sang Sook Kim (Journal of Food Quality)
The aim of the present study was to investigate the influence of milling methods (jet mill (JM) and hammer mill (HM)) and wheat cultivars (Keumkang (K), Jokyung (J), and Anzunbaengi (A)) on physicochemical and dough properties of whole-wheat flour (WWF). The color, particle size, starch damage (SD), falling number (FN), water absorption index (WAI), water solubility index (WSI), pasting and Mixolab® properties, and dough extensibility of WWF were measured. Significant differences were observed in proximate compositions as well as in color, particle size, FN, and WAI between the distinct milling methods and cultivars (p<0.001). The particle sizes of each cultivar milled with a HM (K: 188.5 µm; J: 115.7 µm; A: 40.34 µm) were larger than those milled with a JM (K: 41.8 µm; J: 50.7 µm; A: 20.8 µm). The final viscosity of WWF milled with a HM (K: 1304 cP; J: 1249 cP; A: 1548 cP) was higher than that of cultivars milled with a JM (K: 1092 cP; J: 1062 cP; A: 994 cP). Dough extensibility and resistance to extension also differed among the cultivars, and the C2 Mixolab® parameter (an indicator of protein weakening) was influenced by the milling method. Overall, results from principal component analysis showed that, among the three cultivars, Keumkang WWF was the most affected by the milling method.